Pembuatan Taman Dasawisma Lengkuas sebagai Upaya Peningkatan Ruang Hijau dan Edukasi Lingkungan di Nagari Tanjung, Kabupaten Sijunjung - ramadhani, Selsa; Parma Dewi, Ika; Restu Ramadhani Sopali, Dhea; Zahrand, Emirro; Marlina, Gita; Dwi Nova, Naila; Ramadan , Remil; Sarita Joana, Tasya (Jurnal Pengabdian Kepada Masyarakat Patikala, 2025)
the creation of the Dasawisma Lengkuas park in Nagari Tanjung, Koto VII Subdistrict, Sijunjung Regency, is partof the KKN program of Universitas Negeri Padang in 2025. The goal of this activity is to improve environmental qualityby creating green spaces that can be utilized by the community for education and recreation. This park involved more than100 participants from various segments of the community, including women, youth, and local residents, who participatedin the planning, construction, and maintenance of the park. A total of 10 plants, including fruit trees, flowers, andornamental plants, were successfully planted. The outcomes include increased public awareness about the importance ofmaintaining green spaces, the creation of opportunities for gardening and plant care, and improved air quality around thepark. The park also serves as an educational tool for the local children and residents on environmental conservation. Theactive involvement of the community in park management demonstrates the success of the participatory model in sustainablegreen space development, contributing to improved quality of life and better environmental management. In conclusion, thispark project successfully established a green space that is ecologically, socially, and economically beneficial for the NagariTanjung community.